2013
DOI: 10.1002/mabi.201300273
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Amylose Brushes Revisited: Details from X‐Ray Photoelectron Spectroscopy and Spectroscopic Ellipsometry

Abstract: The successful synthesis of amylose brushes via enzymatic "grafting from" polymerization and the detailed characterization of all synthetic steps by X-ray photoelectron spectroscopy (XPS) and spectroscopic ellipsometry measurements are reported. Au and Si surfaces are amino-functionalized with self-assembled monolayers (SAMs) of cystamine and 3-aminopropyldimethyethoxysilane (APDMES), respectively. Maltoheptaose is covalently attached to the amino-functionalized Au and Si surfaces via reductive amination. Amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Vlist et al synthesized amylose and branched polysaccharide brushes on silica surfaces via enzymatic polymerization . More recently, the same research group used this strategy to modify a gold surface . Such polysaccharide‐grafted surfaces have potential applications as antifouling materials for ship hulls, underwater pipes, and biomedical implants because of the highly hydrophilic nature of the polysaccharide.…”
Section: Enzymatic Synthesis Of Amylose Hybrids By Phosphorylasesmentioning
confidence: 99%
“…Vlist et al synthesized amylose and branched polysaccharide brushes on silica surfaces via enzymatic polymerization . More recently, the same research group used this strategy to modify a gold surface . Such polysaccharide‐grafted surfaces have potential applications as antifouling materials for ship hulls, underwater pipes, and biomedical implants because of the highly hydrophilic nature of the polysaccharide.…”
Section: Enzymatic Synthesis Of Amylose Hybrids By Phosphorylasesmentioning
confidence: 99%
“…In our group, we have successfully prepared many polymers via enzymatic polymerization . Recently, we reported a total green approach for the synthesis of unsaturated poly(butylene succinate‐ co ‐itaconate) (PBSI) by CALB‐catalyzed copolymerization of biobased diethyl succinate, dimethyl itaconate, and 1,4‐butanediol .…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34][35] In our group, we have successfully prepared many polymers via enzymatic polymerization. [36][37][38][39][40][41][42][43] Recently, we reported a total green approach for the synthesis of unsaturated poly(butylene succinate-co -itaconate) (PBSI) by CALB-catalyzed copolymerization of biobased diethyl succinate, dimethyl itaconate, and 1,4-butanediol. [ 38 ] We found that the molar percentage of the unsaturated monomeric segments can be tuned from 0% to 24% by adjusting the feed ratio of itaconate from 0% to 25%.…”
Section: Introductionmentioning
confidence: 99%
“…Reductive amination using NaBH 3 CN as a reducing agent can be used to couple maltoheptaose to the synthesized telechelic amine terminated PTHF. The resulting maltoheptaose‐ b ‐PTHF ‐b ‐maltoheptaose is expected to be able to act as a primer for the enzymatic polymerization of glucose‐1‐phosphate (G 1 P) to prepare amylose‐ b ‐PTHF‐ b ‐amylose . In this case, potato phosphorylase is used as a biocatalyst for the enzymatic polymerization (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting maltoheptaose-b -PTHFb -maltoheptaose is expected to be able to act as a primer for the enzymatic polymerization of glucose-1-phosphate (G 1 P) to prepare amylose-b -PTHF-b -amylose. [29][30][31][32][33] In this case, potato phosphorylase is used as a biocatalyst for the enzymatic polymerization (Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%